Customer experience through online reviews from TripAdvisor - Costa, Sara Morgado da (2023)
Costa, S. M. D., Moro, S., Rita, P., & Alturas, B. (2023). Customer experience through online reviews from TripAdvisor: The case of Orlando theme parks. International Journal of Technology Marketing, 48-77. https://doi.org/10.1504/IJTMKT.2023.127352